التحدّيات عن استخدام الذكاء الاصطناعي في تعليم التَّجويدِ والقِرَاءاتِ: دِراسةٌ تَحْلِيلِيَّةٌ تَقْوِيمِيَّةٌ: Challenges in Using Artificial Intelligence in Teaching al-Tajwīd and al-Qirā’āt: An Analytical and Evaluative Stud - Dr. Muhammad Akram Nizami; Dr Sadia Nasrullah (Al-Amīr Research Journal for Islamic Studies, 2026)
This study offers a comprehensive analysis of the principal challenges associated with integrating artificial intelligence (AI) into the teaching of Tajwīd—a discipline that demands exceptional precision in articulatory accuracy and serves as a safeguard for the sanctity and spiritual depth of Qur’ānic recitation. Despite notable advances in deep-learning algorithms and speech-processing technologies, current AI systems continue to struggle with detecting subtle phonetic distinctions, accommodating the diversity of recitation styles, and recognizing the full spectrum of Qur’ānic readings. The reliability of AI-based evaluation is further constrained by inconsistent audio quality, environmental noise, and the structural complexity of Tajwīd rules—such as ghunnah, madd, idghām, and other intricate phonological phenomena. Additional concerns arise regarding the ability of computational models to reflect the spiritual dimension of recitation, as well as the potential risks associated with excessive learner dependence in the absence of qualified human supervision. Ethical and methodological issues—including data reliability, model bias, and limited generalizability—also pose significant challenges. The study concludes that AI holds considerable promise as a supportive tool in Tajwīd education, provided that it is employed under expert guidance and trained on robust, high-quality, and multi-recitation datasets that ensure both technical accuracy and pedagogical integrity. Keywords: Tajwīd – Artificial Intelligence – Speech Recognition – Qur’ānic Education – Pedagogical Technology – Human Supervision